Analisis Kepuasan Pengguna Website Jurnal Online dengan Menggunakan Metode Webqual (Studi Kasus Buletin Penelitian Sistem Kesehatan) - Nilasari Mukti Widyaningsih; Erma Suryani (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2018)
Research on "Analysis of User SatisfactionWebsite Journal Online using WebQual Method (Case StudyBulletin of Health System Research)" is a study that focuseson assessment website to see views of end-user perception(end user). The perception is illustrated by the relationshipbetween the quality of services or the influence of a websitewith the level of intensity and user satisfaction of onlinejournals.The method used in this study is a quantitative method tomeasure the relationship or influence between the quality ofwebsite services with the level of user satisfaction onlinejournal. To analyze user satisfaction of online journalwebsite in Bulletin of Health System Research usingWebQual theory which is a technique or measurement scaleof website quality based on end user perception (end user).Meanwhile, to see the relationship / influence of usersatisfaction with the intensity of visits to the website, usingthe SEM method (structural equation model).From this research it is known that the quality of the mostinfluential websites on there website user satisfaction on thequality of the information provided in the website. While themost influential in the intensity of visits a website based onresearch results is user satisfaction. So that it can beconcluded that if the manager wants to increase the intensityof the visit the journal website, then the manager shouldimprove the quality of the website, especially the quality ofthe information so that users will be more satisfied in usingthe website.